1998
DOI: 10.1007/s000110050242
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ranitidine on postoperative infectious complications following emergency colorectal surgery: A randomized, placebo-controlled, double-blind trial

Abstract: Ranitidine may have a beneficial effect on postoperative infectious complications in patients following acute colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
(41 reference statements)
2
7
0
1
Order By: Relevance
“…Concerning the septic complications there was an apparent reduction between the ranitidine groups and the others, especially those that received blood transfusions (p<0.001). These findings are in accordance with the mentioned clinical data in which ranitidine may have a beneficial effect on postoperative infectious complications in patients following colorectal surgery [1,6,7].…”
Section: Discussionsupporting
confidence: 94%
“…Concerning the septic complications there was an apparent reduction between the ranitidine groups and the others, especially those that received blood transfusions (p<0.001). These findings are in accordance with the mentioned clinical data in which ranitidine may have a beneficial effect on postoperative infectious complications in patients following colorectal surgery [1,6,7].…”
Section: Discussionsupporting
confidence: 94%
“…Van de Watering et al 21 observed a similar infection rate in patients receiving RBCs filtered before and after storage. In regard to the purported immunosuppressive effect of histamine that accumulates in blood components during storage, 1,2,10 the administration of the histamine 2 receptor antagonist ranitidine to 77 of 164 patients undergoing colorectal surgery (and randomly assigned to receive ranitidine rather than placebo) produced only a marginally lower frequency of postoperative septic complications than that in controls 43 . However, cytokines released from WBCs during storage have been implicated in transfusion reactions, 44 and the length of storage of blood components has been correlated with the frequency of bacterial contamination of the stored components 45 …”
Section: Discussionmentioning
confidence: 99%
“…This was associated with increased phagocytosis and respiratory burst, but lowered CRP and IL-6 levels [101]. Similarly, ranitidine could be shown to modulate postoperative immune response after elective abdominal hysterectomy by lowering IL-6-induced CRP levels [102] and by reducing postoperative infectious complications in patients following acute colorectal surgery [103]. In patients with early states of a systemic inflammatory response after cardiac surgery, pentoxifylline was capable of reducing elastase and soluble selectin levels, and of decreasing the incidence of multiple organ failure [1,104].…”
Section: Potentials Of Immunomodulation To Counteract Surgical Traumamentioning
confidence: 99%